The association of donor age and survival is independent of ischemic time following deceased donor lung transplantation. Issue 7 (1st June 2017) - Mulvihill, Michael S.; Gulack, Brian C.; Ganapathi, Asvin M.; Speicher, Paul J.; Englum, Brian R.; Hirji, Sameer A.; Snyder, Laurie D.; Davis, R. Duane; Hartwig, Matthew G.
Abstract: Purpose: Early research suggests prolonged ischemic time in older donor lungs is associated with decreased survival following lung transplantation. The purpose of this study was to determine whether this association holds in the post‐lung allocation score era. Methods: We analyzed the United Network for Organ Sharing database 2005‐2013 for adult recipients of cadaveric lung transplants. Cox proportional hazards modeling was utilized to determine the association of donor age, ischemic time, and the interaction of donor age and ischemic time with transplant‐free survival. Results: Eleven thousand eight hundred thirty‐five patients met criteria. Median donor age was 32 years, and median ischemic time was 4.9 hours. Cox modeling demonstrated that donor age 50‐60 (adjusted hazard ratio (HR): 1.11) and ≥60 (adjusted HR: 1.42) were associated with reduced overall survival. Neither ischemic time nor interaction of ischemic time and donor age were significantly associated with overall survival. Subanalysis demonstrated that this finding held true for patients undergoing either single or bilateral lung transplantation. Conclusions: Prolonged ischemic time is not associated with decreased overall survival in patients undergoing lung transplantation regardless of the donor's age. However, donor age >50 is independently associated with decreased survival. The lack of an association between ischemic time and survival should encourage broader geographic allocation of pulmonary allografts.